Utilizing ChatGPT in Academic Writing: A Literature Review - Valenzuela, Christian Loid (PT FORMOSA CENDEKIA GLOBAL, 2024)
This literature review focuses on documenting the perceived potentials and risks of utilizing ChatGPT in academic writing by providing an in-depth exploration from available studies online or in print. Through this literature review, the researcher aimed to provide a research-based insights towards the integration of ChatGPT in education settings. In line with this, this paper may assist educators, students or related stakeholders to have a sound judgement, critical analysis and objective perception on utilizing ChatGPT in the field of education